Etude de la qualité des eaux de baignade de la plage de Sonacter - Benhalima, Amina; Elahouel, Halima (My University, 2022)
The sea has always been considered as a universal receptacle for all forms of pollution generated by human activities, which have systematically led to physico-chemical and bacterial pollution at the level of the coast, thus creating an ecological imbalance and pathogenic and epidermal manifestations. The objective of our work is to assess the physicochemical quality of bathing waters to protect human health. We assessed the quality of the Sonacter beach for three months: March-April-May, while carrying out the analysis: of parameters: physicochemical: pH, conductivity, temperature, dissolved oxygen, salinity and suspended matter. The analysis of the results obtained shows that, qualitatively, the water of the beach is characterized by the following physico-chemical parameters: The alkaline pH is between (8.02_ 8.73) The conductivity is between (51800 μs/cm _56200 μs/cm) The dissolved oxygen is between (3.5mg/l _8.62 mg/l) The salinity is between (36 ‰ _34.1 ‰) The suspended matter is between (3.8mg/l_48mg/l) All the results collected from the bathing waters at the Sonacter beach are below the mandatory values set, and generally present poor quality. Analyzes of physico-chemical parameters make it possible to determine and know the level of contamination of seawater, but give little information on its "biological quality".
Keywords: pollution; sonacter beach; Seawater; Setting physicoc hemical; bathing water